PENERAPAN MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISIONS UNTUK MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VIIA SMP NEGERI 1 KALIBAWANG - Destri Setyawati; Benedictus Kusmanto (UNION: Jurnal Ilmiah Pendidikan Matematika, 2015)
An application of cooperative learning model type Students Teams Achievement Division (STAD) to increase the effectiveness and achievement in learning mathematics of students grade VII A SMP Negeri 1 Kalibawang, Kulon Progo in year 2013/ 2014. The type of this research is classroom action research collaboratively. The subject of the reasearch are students grade VII A SMP Negeri Kalibawang, Kulonprogo. It consist 35 students. The object of the research isÂ  the effectiveness and studentsâ€™ achivement in learning mathematics through cooperative learning model type Students Teams Achievement Division (STAD). The result shows the increase by using this model. It is shown by the increase of the subjection mean in observation sheet in each cycle. Pre-cycle of the effectivenes shows 62,86% become 72,14% in cycle I, then it has an increase in cycle II become 83,81%. Beside that, the subjection mean of students achievement has an increase. In pre-cycle shows 54,14 with Kriteria Ketuntasan Minimum (KKM) is 31,43% consist of 8 students, in cycle I has an increase become 65,51 with KKM is 48,57% consist of 17 students, whereas in cycle II shows the increse become 75,13 with KKM is 77,14%.